Free to improve? The impact of free school attendance in England - Marco Bertoni; Gabriel Heller-Sahlgren; Olmo Silva (Research Institute of Industrial Economics (IFN), 2023)
We investigate the impact of attending a free school in England - that is, a new start-up school that enjoys considerable autonomy while remaining in the state sector. We analyse the effects of two secondary free schools with different teaching philosophies: one follows a "no excuse" paradigm, while the other one adopts a "classical liberal", knowledge-rich approach. We establish causal effects exploiting admission lotteries and a distance-based regression discontinuity design. Both schools have a strong positive impact on student test scores on average. However, we also find heterogeneous effects: the "no excuse" school mostly benefits boys, while the "classical liberal" school mainly benefits White British and non-poor students. Both schools similarly reduce student absences and school mobility. Peer quality, teacher characteristics, and inspectorate ratings cannot fully explain the schools' effectiveness. Instead, a quantitative text analysis of the schools' "vision and ethos" statements shows that the "no excuse" and "classical liberal" philosophies adopted by the two free schools clearly set them apart from the counterfactual schools where rejected applicants enrol, and likely explain their heterogeneous effects.
Keywords: I21; I24; I28; 330; school autonomy; quasi-markets; free schools; achievement